Transnational banks and the international debt crisis - Mortimore, Michael...[et al] (United Nations New YorkUS, 1991)
Provides an overview of the sovereign lending boom of 1974-1982 and the debt-restructuring process 1983-1987. Presents case studies which give new insights into the differential behaviour of transnational banks. Highlights the principal weakness of the debt-restructuring process.